MEMBANGUN DESA MANDIRI UDANG VANAME: PENDAMPINGAN MAHASISWA DALAM MENINGKATKAN KUALITAS AIR KOLAM BUNDAR UDANG VANAME DI DESA BUGEMAN - Abdul Wafi; Ach. Khumaidi; Abdul Muqsith (As-Sidanah, 2024)
Bugeman Village has great potential for vaname shrimp farming. However, vaname shrimp production in this village is still hindered by suboptimal pond water quality. This has resulted in high shrimp mortality rates and low yields. This community service aims to improve the water quality of round vaname shrimp ponds (KODAME) in Bugeman Village through mentoring undergraduate students studying water quality management. Water quality is very important for the aquaculture process as it can help increase aquaculture productivity and prevent environmental damage. Students will provide training to shrimp farmers on effective pond water management techniques, such as measuring water quality parameters, regulating aeration and filtration, and using probiotics. This program is expected to improve the water quality of shrimp farmers' ponds in Bugeman Village, thereby increasing shrimp production and increasing their income. Bugeman Village is expected to become a self-reliant vaname shrimp village that can improve the welfare of its people. In addition to training, students will also assist shrimp farmers in implementing the learned pond water management techniques. Students will also monitor and evaluate this program to ensure its effectiveness. It is hoped that this program can make a significant contribution to the development of vaname shrimp farming in Bugeman Village and improve the welfare of its people.